2016
DOI: 10.1177/000313481608200942
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Adjuvant Radioactive Iodine Therapy Does Not Affect Overall Survival in Low- and Intermediate-Risk Papillary Thyroid Carcinoma

Abstract: There is no consensus regarding the timing of adjuvant radioactive iodine therapy (RAI) therapy in low- and intermediate-risk papillary thyroid carcinoma (PTC). We analyzed the impact of adjuvant RAI on overall survival (OS) in low- and intermediate-risk PTC. The National Cancer Data Base was queried from 2004 to 2011 for pN0M0 PTC patients having near/subtotal or total thyroidectomy and adjuvant RAI. Tumors ≤1 cm with negative margins were low risk while 1.1- to 4-cm tumors with negative margins or ≤1 cm with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 16 publications
1
32
1
Order By: Relevance
“…Higashi et al have investigated the effects of delayed RAI therapy (more than 180 d) on OS in 198 metastatic patients with DTC and indicated that the risk of death was 4.22 times higher in metastatic patients with delayed RAI treatment. Other studies presented contrary conclusions, indicating that delayed RAI would not affect the OS in patients in all categories of TNM stage and ATA risk stratification . Tsirona et al demonstrated that the timing of RAI did not impact remission in limited numbers of low‐risk DTC.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Higashi et al have investigated the effects of delayed RAI therapy (more than 180 d) on OS in 198 metastatic patients with DTC and indicated that the risk of death was 4.22 times higher in metastatic patients with delayed RAI treatment. Other studies presented contrary conclusions, indicating that delayed RAI would not affect the OS in patients in all categories of TNM stage and ATA risk stratification . Tsirona et al demonstrated that the timing of RAI did not impact remission in limited numbers of low‐risk DTC.…”
Section: Discussionmentioning
confidence: 96%
“…Whether the initiating time will affect the clinical outcome of RAI treatment remains uncertain. Few clinical studies have focused on this issue with controversial conclusions . Higashi et al reported that delayed RAI therapy (>180 days after total thyroidectomy) may result in poor survival for DTC compared with early RAI therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings confirm that, in properly selected patients with low or intermediate risk of recurrence, in whom the use of RAI is selective, the behavior of Tg and TgAb during follow-up can modulate the indication for RAI. Furthermore, previous studies have shown that in low-and intermediate-risk patients, the efficacy of RAI is preserved even if administered up to one year after surgery, giving the clinician enough time to thoroughly decide its indication (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…In routine practice, the time for patients from finishing enhanced CT examination to starting RAI therapy is far more than 43 days. Moreover, the majority of studies showed that the timing of post-thyroidectomy initial RAI therapy did not affect the overall survival or long-term outcomes (33)(34)(35)(36)(37)(38). Therefore, RAI administration may be safely planned according to the logistics of the local health and the patient itself.…”
Section: Discussionmentioning
confidence: 99%